LA CRAVATE ET LA MONTRE SEBUAH KALIGRAM KARYA APOLLINAIRE : ANALISIS SEMIOTIK - Armini, Alice (Diksi, 2006)
rpieces remain timeless and his influence on the world of literature and artare greatly felt. The way typographical poetry, which is a kind of visual poetry orcalligram, is presented is extremely interesting and this article intends to describethe relation between the meaning of the words in the calligram and its pictorialform in one of Apollinaire's poems in the form of a calligram titled "La Cravate etLa Montre."The term calligram means "Belle Ecriture", that is, "beautiful writing",coming from the Greek words kallos, meaning "beautiful", and gramma, meaning"writing'. So a calligram work of art, also called visual poetry and typographicalpoetry, is a poem or poetic lines or lines of poetic words arranged in such a way thata picture is formed. To comprehend, enjoy, and appreciate well a poetical work,one needs to examine its various aspects. A poem in the form of a calligram needsto be structurally and semiotically analyzed. By means of such analysis, its fullmeaning could be obtained and it can be comprehended as a work of art with poeticvalues.The poem concerned here is a monologue coming from "I" to "you". Thisis strengthened by the presence of the subject on, meaning "we", the phrase monCoeur, meaning "my heart", and the phrase ton corps, meaning "your body". "I"intends to deliver an important message to mankind about life as a journey towardsdeath. One's life time in this world is extremely short so that one should spend thetime doing useful things. So a happy person is someone who makes use of time toenjoy life with freedom from strict rules. Life should not be burdened with manyrules that bind freedom. In Latin such a view is expressed in the phrase CarpeDiem, which corresponds to the French Mets í  profit le jour présent. This isreflected in the tie and clock shapes of the poem. A tie worn on the neck causes aconstricted feeling making one feels unable to breathe freely so that it must betaken off. The clock shape is used to refer to the passing of time illustrating life as ajourney towards God and death.Keywords: calligram, typographical poetry, iconicity